Aplikasi Mikroenkapsulasi Lactobacillus acidophilus dalam Butter Buah Nanas (Ananas comosus (L). Merr.) - lestari, Diana; Marvina, Marvina; Pramitasari, Rianita (JURNAL AGROINDUSTRI HALAL, 2020)
Microencapsulation is a technique that can improve the viability of probiotics and protect the cells from adverse environment by entrapping the cell inside a bead matrix. Probiotic strains Lactobacillus acidophilus was microencapsulated by an emulsion method using sodium alginate, palm oil, and Tween 80. The aim of this research were to produce microencapsulated L. acidophilus by emulsion method and evaluate the stability of microencapsulated probiotic during storage in pineapple fruit butter. Microencapsulation could protect probiotic during storage (significantly different (p=0,05)) than without microencapsulation. During two weeks storage, free cells decreased dramatically (2,5 log CFU/g) than encapsulated cells (1,2 log CFU/g). Storaging microencasulated probiotic in refrigerator temperature (4°C) caused microencapsulated probiotic had longer shelf life (22 days) than room temperature (9 days). pH of pineapple butter containing microencapsulated probiotic cells were found as more stable during storage than were the free cells.